Integrating business management processes. Volume 1, Management and core processes - De Silva, Titus (New York, NY : Routledge, 2021)
Integrating Business Management Processes: Management and Core Processes (978-0-367-48549-8, 365816) Shelving Guide: Business & Management The backbone of any organisation is its management system. It must reflect the needs of the organisation and the requirements of its customers. Compliance with legal requirements and ethical environmental practices contributes towards the sustainability of the management system. Whatever the state of maturity of the management, this book, one of three, provides useful guidance to design, implement, maintain and improve its effectiveness. This volume, with its series of examples and procedures, shows how organizations can benefit from satisfying customer requirements and the requirements of ISO standards to gain entry into lucrative markets. It provides a comprehensive coverage of the key management and core processes. Topics include the impact of management systems on business performance, strategic planning, risk management, good manufacturing practices, purchasing, production and provision of services, new product planning, warehousing and logistics, sales management and several other topics. This book, along with its two companion volumes, is a practical guide for real managers, designed to help them manage their business more effectively and gain competitive advantage. Titus De Silva is a consultant in management skills development, pharmacy practice, quality management and food safety and an advisor to the newly established National Medicines Regulatory Authority (NMRA) in Sri Lanka.
3.6.8 Establish a Vision -- 3.6.8.1 Vision Statement -- 3.6.9 Develop an Implementation Plan -- 3.6.10 Strategy-Focused Organisation: Balanced Score Card -- 3.6.10.1 Principle 1 -- 3.6.10.2 Principle 2 -- 3.6.10.3 Principle 3 -- 3.6.10.4 Principle 4 -- 3.6.10.5 Principle 5 -- 3.6.11 Final Assessment -- 3.6.11.1 Frequency of Monitoring and Evaluation -- 3.6.11.2 Monitoring Reports -- 3.6.11.3 Deviations from the Plan -- 3.6.11.4 Changing the Plan -- 3.7 Failure of Strategy Implementation -- References -- 4 Risk Management -- 4.1 Introduction -- 4.2 The Evolution of Risk Management -- 4.3 Terminology.
"A Productivity Press book."
OCLC-licensed vendor bibliographic record.
Keywords: Industrial management; Environmental management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning